Construction of an enzymatic biosensor for chlorpyrifos pesticide detection via acetylcholinesterase inhibition on oxidative boron-doped diamond electrode - Basit, Abdul; Ferinastiti; Tesla, Yudhistira; Naumi, Fadlinatin (Environmental and Materials, 2024)
Background: The extensive utilization of pesticides in agricultural practices presents considerable environmental and health hazards, which calls for the creation of precise and specialized detection techniques. Methods: This study focuses on the development of an enzymatic biosensor designed to detect chlorpyrifos pesticide residues. The biosensor employs an oxidative boron-doped diamond (OBDD) electrode as the transducer platform, offering exceptional sensitivity and stability. The detection mechanism is based on the inhibition of acetylcholinesterase (AChE) activity on the OBDD surface. Various factors were optimized to assess the precision and sensitivity limit of the developed sensor. The cyclic voltammetry (CV) results indicated that the presence of AChE is necessary for acetylthiocholine chloride (ATCl) to generate an electrical signal. To enhance detection, AChE was modified with magnetic beads. Findings: This modification facilitated the oxidation of ATCl to thiocholine chloride, an oxidation peak of thiocholine could be observed at the magnetic beads modified AChE-Biotin/OBDD at a potential of +0.804 V (vs. Ag/AgCl), formed by an enzymatic reaction of AChE in the presence of acetylthiocholine. The current signal decreased due to the inhibition of AChE activity by chlorpyrifos pesticide. The oxidation current of thiocholine chloride consistently decreased as the chlorpyrifos concentration increased within the range of 0.001nM to 10nM at the optimum condition of 50 mM phosphate buffer solution pH 7.6; 250 mu/5 mL AChE; and 1 mM ATCl in an inhibition and contact time of 30 and 15 min, respectively. The regression equation obtained using magnetic beads modified by AChE-Biotin is y = 0.043ln(x) + 1.074, with an R² value of 0.9062. The sensor demonstrated a lower limit of detection value of 0.6551nM. Conclusion: Furthermore, the developed sensor proved suitable for testing real samples of tap water, showing minimal interference with a % RSD value lower than 10%. Novelty/Originality of this Study: This study introduces a novel enzyme-based biosensor using oxidative boron-doped diamond (OBDD) electrodes for detecting chlorpyrifos pesticide. The originality lies in the use of electrochemically modified BDD, which enhances enzyme immobilization and stability, providing higher sensitivity and lower detection limits compared to traditional methods.